Andean archeology: new actors and analysis - Zegarra Moretti, Carlos Benjamín (2012)
This issue of Allpanchis offers articles that deal —in an original way with Peruvian archeology, which tends to focus its efforts on civilizations and cultures during the pre-Hispanic period— with actors and spaces that have not yet been sufficiently analyzed. The African population in the viceregal estates, the islands of the Peruvian sea and the second settlement of the Spanish city of San Miguel de Piura are the topics that the contributors to this issue on Andean archeology occupy.